SELECTION RESPONSE FOR INCREASED GRAIN YIELD IN TWO HIGH OIL MAIZE SYNTHETICS - Made J. Mejaya; R.J. Lambert (Indonesian Agency for Agricultural Research and Development, 2007)
Selection for increased oil level in maize showed the increase was associated with decrease in starch concentration, kernel weight, and grain yield. The study was conducted with the objectives: (1) to evaluate response to six cycles for increased grain yield in the high oil maize Alexho Elite (AE: 60-90 g kg-1 oil concentration) and Ultra High Oil (UHO: 100-140 g kg-1 oil concentration) using inbred tester B73; (2) to measure responses to selection for increased grain yield with changes in yield components; and (3) to determine a suitable tester. Previously the two synthetics had been selected for oil concentration. After six cycles, the six genotypes i.e. AE C0, AE C3, AE C6, UHO C0, UHO C3, and UHO C6 were testcrossed to B73, LH185, and LH202 inbreds (40 g kg-1 oil concentration) to a total of 18 testcrosses. Two field experiments were used to evaluate selection in AE and UHO testcrosses. The study showed selection using inbred tester B73 in AE and UHO was effective in increasing grain yield of AE testcrosses without changing (i.e. decreasing) oil and protein concentrations. AE testcrosses produced higher grain yield and greater selection response for grain yield than UHO testcrosses. LH185 was best for grain yield in AE and UHO testcrosses. Increase in grain yield in most of the testcrosses was associated with increases in starch concentration, kernel weight, kernel number, and grain weight.